2021
DOI: 10.3389/fonc.2021.703465
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oral Arginase 1/2 Inhibitor Enhances the Antitumor Effect of PD-1 Inhibition in Murine Experimental Gliomas by Altering the Immunosuppressive Environment

Abstract: Glioblastomas (GBM) are the common and aggressive primary brain tumors that are incurable by conventional therapies. Immunotherapy with immune checkpoint inhibitors is not effective in GBM patients due to the highly immunosuppressive tumor microenvironment (TME) restraining the infiltration and activation of cytotoxic T cells. Clinical and experimental studies showed the upregulation of expression of the arginase 1 and 2 (ARG1 and ARG2, respectively) in murine and human GBMs. The elevated arginase activity lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…5a). Both arginase inhibitor (ARGi, OAT-1746, a membrane-permeable, potent inhibitor of both arginase isoforms [22][23][24] ) and ROS inhibitor (ROSi, N-acetylcysteine) nearly completely restored the proliferation of T-cells that was inhibited by co-culture with CECs isolated from NHA mice (Fig. 5b), similar to CECs isolated from neonates (Supplementary Fig.…”
Section: Cecs Degrade L-arg and Produce Ros Leading To The Suppression Of T-cellssupporting
confidence: 53%
“…5a). Both arginase inhibitor (ARGi, OAT-1746, a membrane-permeable, potent inhibitor of both arginase isoforms [22][23][24] ) and ROS inhibitor (ROSi, N-acetylcysteine) nearly completely restored the proliferation of T-cells that was inhibited by co-culture with CECs isolated from NHA mice (Fig. 5b), similar to CECs isolated from neonates (Supplementary Fig.…”
Section: Cecs Degrade L-arg and Produce Ros Leading To The Suppression Of T-cellssupporting
confidence: 53%
“…Although these data show the potential antigen presentation capabilities of GAMs, scRNA-seq analysis of murine and human gliomas has also shown the immunosuppressive nature of these myeloid cells. For instance, one study showed that ARG1/2 was upregulated predominantly in glioma-associated macrophages as opposed to microglia ( 49 ). This was further corroborated by elevated arginase-1 levels synthesized by tumor-infiltrating macrophages from mouse and human gliomas that promote the generation of polyamines and thus, T cell suppression ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since PD-1-expression in the TAM compartment is heterogenous and not all TAMs are positive for PD-1 [ 51 ], a second TAM-targeted therapy may also be relevant in this case. One such example is the concomitant use of an Arginase inhibitor that increased the anti-tumor activity of a PD-1 inhibitor in murine gliomas [ 147 ]. However, the significance of Arginase and its inhibition in human GBM will have to be clarified before clinical translation of this strategy.…”
Section: Therapeutic Options For Targeting Tamsmentioning
confidence: 99%